What Is the Role of AI in Interventional Radiology? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2017)
Interventional Radiology (IR) and Artificial Intelligence (AI) are two fields at the forefront of technological innovation in medicine. While AI has already ...
Keywords: AI in Medical Imaging and Diagnostics; Interventional; Radiology; Artificial Intelligence; Machine Learning; Deep Learning; Precision Medicine